THE EFFECTIVENESS OF MORAL LEARNING USING INTERACTIVE MEDIA IN SECONDARY SCHOOLS - Amstrong Harefa; Simanjuntak, Rosmerry; Sutrisman, Henny (International Journal of Teaching and Learning, 2024)
Interactive media in moral learning is the use of various digital tools such as educational games, simulations and interactive videos to support the process of teaching moral values ​​and good attitudes. This media aims to increase student involvement and provide a more in-depth and personalized learning experience, enabling students to understand and internalize moral values ​​more effectively. The study in this research uses literature research methods. This research concludes that the use of interactive media significantly increases students' involvement and understanding in the context of learning morality knowledge. For students who receive interactive media education, active engagement is higher, and they are able to find connections between moral values ​​and real-life situations, which significantly deepens their students' understanding of the consequences of their actions. Additionally, popular interactivity provides real-time feedback opportunities, meaning that timely and personalized corrections provide the motivation for clearer and more effective directional cues, and more effective and efficient classroom management. Simultaneously, despite the importance of digital elements in teaching ethics, the literature points to the importance of integrating online strategies with traditional methods so that the learning environment is holistic and balanced. Thus, interactive media will prove its effects, to a certain extent, based on a consistent relationship with comprehensive understanding. These findings collectively confirm the relevance of improving technology infrastructure and teacher skills for its use to provide the greatest benefit.